A traceable physical calibration of the vertical advection‐diffusion equation for modeling ocean heat uptake. Issue 7 (3rd April 2015) - Huber, Markus; Tailleux, Remi; Ferreira, David; Kuhlbrodt, Till; Gregory, Jonathan
Abstract The classic vertical advection‐diffusion (VAD) balance is a central concept in studying the ocean heat budget, in particular in simple climate models (SCMs). Here we present a new framework to calibrate the parameters of the VAD equation to the vertical ocean heat balance of two fully‐coupled climate models that is traceable to the models' circulation as well as to vertical mixing and diffusion processes. Based on temperature diagnostics, we derive an effective vertical velocity w∗ and turbulent diffusivity <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgjk2t24cp" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />kν∗</alternatives> for each individual physical process. In steady state, we find that the residual vertical velocity and diffusivity change sign in middepth, highlighting the different regional contributions of isopycnal and diapycnal diffusion in balancing the models' residual advection and vertical mixing. We quantify the impacts of the time evolution of the effective quantities under a transient 1% CO2 simulation and make the link to the parameters of currently employed SCMs.